Keperawatan medikal bedah / Mary DiGiulio, Donna Jackson dan Jim Keogh; Penerjemah, Dwi Prabantini; Ediotr, Arie Prabawati, Meidyna dan Khudazi Aulawi - DIGIULIO, Mary; ARIE Prabawati; DWI Prabantini; JACKSON, Donna; KEOGH, Jim; KHUDAZI Aulawi; MEIDYNA; The McGraw-Hill (Rapha Publishing, 2014)
xvi, 609 hlm. : ilus. ; 23 cm.